Kesetaraan Gender Dalam Perspektif Al-Qur’an (Studi Komparatif Tafsir Ibnu Katsir Dan Al-Mishbah) - Alharira Eisyi Latifah; Dudin Shobbaruddin (Kopertais Wilayah XV Lampung, 2022)
Religion is often indicated by gender inequality. Gender equality has always been the subject of controversy, especially in explaining, interpreting and determining laws between women and men. Ibnu Katsir and M. Quraish Shihab have similarities and differences in interpreting gender equality verses. This study aims to find out the interpretation of gender equality verses according to classical and contemporary commentators Ibnu Katsir and M. Quraish Shihab, look for similarities and differences in the interpretations of Ibnu Katsir and M. Quraish Shihab and find out the relevance of gender equality in the perspective of the Qur'an. This type of research uses library research. Then analyzed by descriptive-comparative method, carried out by documentation techniques, analysis, comparisons, and checking the validity of the data to get research results according to the objectives. The results of this study indicate that the thoughts of Ibnu Katsir and M. Quraish Shihab regarding gender equality have similarities in seeing gender equality in several verses of the Qur'an which do not distinguish between the positions of women and men and there are differences in thinking based on surah An-Nisa : 34 about leadership. Differences in times, conditions, situations and civilizations that influence it. Based on this research too, it can be concluded that the Qur'an emphasizes that Islam upholds gender equality. Gender equality is part of Islamic values ​​that apply universally.